A farm typology development cycle: From empirical development through validation, to large-scale organisational deployment - Manners, Rhys; Hammond, James; Umugabe, David Renaud; Sibomana, Milindi; Schut, Marc (Elsevier, 2025)
CONTEXT: The publication of farm (or farmer) typologies has increased over recent years. The purpose of these studies is usually to differentiate groups of farmers so that they are “targeted” with specific agricultural innovations, or best-bet interventions can be “prioritised”. The degree to which such typologies actually influence development practice is however unclear, and little has been published on that topic.